PENGARUH ETIKA TERHADAP MUTU PELAYANAN LOKET PENDAFTARAN PASIEN RAWAT JALAN RUMAH SAKIT UNIVERSITAS MATARAM - Fatriyawan, Abdul Aziz; Arsi Safitri (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Mataram University Hospital is a hospital belonging to the Ministry of Research and Technology of Higher Education (Kemenristekdikti) which is authorized to the Chancellor of the University of Mataram and has a vision of becoming a superior hospital with comprehensive services and involving multidisciplinary activities to improve the health status of the community by implementing service ethics, especially the section registration counter which is the spearhead of the hospital itself or the first service that is passed by the patient. This research is an analytical observational research, namely research that tries to explore the research data design and uses data sourced from respondents and documentation of the Mataram University Hospital. The sample of this study were 97 respondents who were outpatients at the Mataram University Hospital. Based on the results of research and discussion on the influence of outpatient ethics at the Mataram University Hospital, it has a significant effect on service quality, namely as much as 61.9% individually.